Dekomposisi Perubahan Ketimpangan di Indonesia Tahun 2005-2014 - Ananda Dellina Putri; Teguh Dartanto (Universitas Negeri Malang, 2016)
Income inequality in Indonesia has been worse for the past ten years, therefore the right policy is really needed to reduce inequality. However, to know what is the right policy that can reduce income inequality, studies about the inequality itself is necessary. The purpose of this study is to give picture about in what condition high inequality happened and why inequality increased. The methods used are static decomposition and decomposition of changes inequality or dynamic decomposition. The result of this study show that highest inequality happened between population with different education level of household head. There was indication that education level of household head already increased, but it still did not contribute significantly to reduce inequality. Therefore to reduce inequality, Indonesian people should be supported to increase their education level. Keywords: changes inequality; dynamic decomposition; inequality; static decomposition